Fenomena FOMO dan Konsumsi Fashion Pada Mahasiswa UIN Ar-Raniry Banda Aceh Di Era Komunikai Digital - Fithrah Ibnayyah; Elfina Rahmatin; Suqya Rahmatin; Taufik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study explores the phenomenon of Fear of Missing Out (FoMO) and fashion consumption behavior among Generation Z university students in Banda Aceh in the era of digital communication. The research is grounded in the growing use of social media platforms such as TikTok and Instagram, which have shaped new consumption patterns based on trends and social validation. The purpose of this study is to examine how digital communication and FoMO influence fashion purchasing decisions, as well as to identify the underlying social and psychological factors. Using a descriptive qualitative approach, data were collected through in-depth interviews with several active social media users who have purchased fashion products influenced by online trends. The findings reveal that most respondents purchase new clothing, shoes, or accessories even when the old ones are still wearable, driven by the desire to stay relevant to current viral trends. Repetitive exposure to fashion content, influencer endorsements, and digital marketing strategies significantly increase buying interest and reinforce symbolic consumption behavior. FoMO also triggers social anxiety that compels individuals to follow trends to maintain their digital presence. Nevertheless, some respondents show financial awareness by considering their economic capacity and family values before purchasing. This study concludes that Generation Z’s fashion consumption behavior is a complex result of digital communication, social pressure, and psychological needs for belonging within virtual communities. Keywords: Fear of Missing Out, fashion consumption, digital communication, Generation Z